Input-selective adenosine A1 receptor-mediated synaptic depression of excitatory transmission in dorsal striatum - Brandon M. Fritz (Nature Portfolio, 2021)
Abstract The medial (DMS) and lateral (DLS) dorsal striatum differentially drive goal-directed and habitual/compulsive behaviors, respectively, and are implicated in a variety of neuropsychiatric disorders. These subregions receive distinct inputs from cortical and thalamic regions which uniquely determine dorsal striatal activity and function. Adenosine A1 receptors (A1Rs) are prolific within striatum and regulate excitatory glutamate transmission. Thus, A1Rs may have regionally-specific effects on neuroadaptive processes which may ultimately influence striatally-mediated behaviors. The occurrence of A1R-driven plasticity at specific excitatory inputs to dorsal striatum is currently unknown. To better understand how A1Rs may influence these behaviors, we first sought to understand how A1Rs modulate these distinct inputs. We evaluated A1R-mediated inhibition of cortico- and thalamostriatal transmission using in vitro whole-cell, patch clamp slice electrophysiology recordings in medium spiny neurons from both the DLS and DMS of C57BL/6J mice in conjunction with optogenetic approaches. In addition, conditional A1R KO mice lacking A1Rs at specific striatal inputs to DMS and DLS were generated to directly determine the role of these presynaptic A1Rs on the measured electrophysiological responses. Activation of presynaptic A1Rs produced significant and prolonged synaptic depression (A1R-SD) of excitatory transmission in the both the DLS and DMS of male and female animals. Our findings indicate that A1R-SD at corticostriatal and thalamostriatal inputs to DLS can be additive and that A1R-SD in DMS occurs primarily at thalamostriatal inputs. These findings advance the field’s understanding of the functional roles of A1Rs in striatum and implicate their potential contribution to neuropsychiatric diseases.